SENTIMENT ANALYSIS OF BIG DATA TO MEASURE TOURISM'S SOCIAL AND EMOTIONAL IMPACT ON SOCIAL MEDIA: A CASE STUDY OF INDONESIA - Diego Romario De Fretes; Henny Noviany; Evie Farida Juliarta; Deasy Sandya, Adrie Charviandi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This study employed advanced sentiment analysis techniques on extensive social media datasets to examine the social and emotional impact of tourism, with a focus on the Indonesian context. The research provided nuanced insights into the complex interplay between tourism experiences and digital narratives by delving into sentiment variations and identifying prevalent emotional factors within online discourse. The study aimed to understand the evolving role of social media in shaping travel trends and explored the broader implications of tourism on societal dynamics and individual wellbeing. Findings from this research contributed to a comprehensive understanding of sentiments across diverse destinations, offering valuable insights for stakeholders in the tourism sector. For instance, positive sentiments dominated the discourse, comprising 68% of overall reactions, indicating a robust enthusiasm for Indonesia's tourism experiences. Negative sentiments accounted for 22%, signaling areas of concern or dissatisfaction, while the remaining 10% encompassed neutral sentiments, reflecting objective discussions. Additionally, the study discussed implications for tourism policy development, emphasizing the need for strategies that balance economic benefits with social and environmental considerations. By bridging quantitative and qualitative perspectives, this research aimed to facilitate informed decision-making and strategic planning within the dynamic landscape of the tourism industry, fostering sustainable practices and positive societal impacts.